Binge drinking: Burden of liver disease and beyond - Llerena, Susana (World J Hepatol, 2015)
The consumption of alcoholic beverages is harmful to human health. In recent years, consumption patterns of alcoholic beverages have changed in our society, and binge drinking has generalized. It is considered to be a socio-sanitary problem with few known consequences in terms of individual and third-party social impacts (in the form of violence or traffic accidents) and its organic impact (affects the liver and other organs and systems, such as the nervous and cardiovascular systems) and represents an important financial burden due to its increasing economic impact. This review provides a global approach to binge drinking and emphasizes its epidemiological character, the effect of this type of consumption and the possible management of a problem with an increasing tendency in our society.